Microfluidics‐Assisted Osteogenesis: Injectable Stem Cell‐Laden Photocrosslinkable Microspheres Fabricated Using Microfluidics for Rapid Generation of Osteogenic Tissue Constructs (Adv. Funct. Mater. 17/2016). (May 2016) - Zhao, Xin; Liu, Shen; Yildirimer, Lara; Zhao, Hong; Ding, Ruihua; Wang, Huanan; Cui, Wenguo; Weitz, David
Abstract : A bone regeneration strategy with minimum invasiveness is developed on page 2809 by W. Cui, D. Weitz, and co‐workers, using microfluidics‐fabricated photocrosslinkable gelatin microspheres encapsulating bone marrow‐derived mesenchymal stem cells and growth factors. The cell‐laden microspheres are found to enhance and accelerate osteogenesis in vitro and in vivo, associated with a significant increase in mineralization.